Unbalanced distribution of electric current in underwater electrical wire array explosion. (5th May 2022) - Liu, Zhigang; Qian, Dun; Xu, Cong; Li, Liuxia; Zou, Xiaobing; Wang, Xinxin
Abstract: The uniformity of electric current distribution in a wire array and its unstable behavior during the process of underwater electrical explosion have been investigated. Two exploding wires in parallel were used in the experiments and the current waveforms flowing through each wire were obtained using two self-integrating coils. Significant differences in the current waveforms of the two wires were observed near the melting point, which was attributed to the non-simultaneity of heating and phase transition. Unbalanced current distribution caused by the deviations of wire dimensions was analyzed based on a magneto-hydrodynamic model, and the simulation results show that thermodynamic state difference between two wires is present throughout the entire electrical explosion process. It is also found that the initial stored energy of pulse generator will affect the thermodynamic state evolution of exploding wires, resulting in different behaviors of current distribution after the explosion time. The slightly different heating rate caused by unbalanced current distribution in a wire array can break the symmetry of converging shock waves and lower the pressure peak in the vicinity of implosion axis, which was discussed based on the two-dimensional hydrodynamic simulations.